Histoire de la Troisième République - Zevort, Edgar (1842-1908)
I. La présidence de M. Thiers. - 1896 ; II. La présidence du Maréchal. - 1897 ; III. La présidence de Jules Grévy. - 1898 ; IV. La présidence de Carnot. - 1901